Método para alocação de métricas de impacto ambiental em unidades industriais multiproduto - Oliveira, Alexchéviny Gimenez (Universidade Federal de São Carlos, 2023)
Life cycle assessment is an environmental, economic, and social evaluation technique focused on understanding and quantifying the impacts related to a particular product, good, or service. This assessment considers all stages in which it performs its function, from obtaining resources for production to final disposal. Often, the production stage generates various marketable products, such as in biorefineries, industries whose backbone is the production of biofuels along with a portfolio of other higher-value-added products. Although the contribution of industrial processing to environmental impact is typically lower than that of the agricultural sector, it is from the gates of these multiproduct processes that the final products emerge. Thus, the method employed for allocating environmental impact indices to the various products plays a crucial role in valuing, comparing, and improving production processes. However, there is still no consensus on the most appropriate allocation method. In this context, the objective of this study was to develop a systematic, first-principles-based method for detailed accounting of impacts throughout the industrial process. The new proposed method was compared to the global allocation approach, taking as a case study a sugarcane biorefinery producing ethanol and electricity. In this case study, the proposed allocation method calculated an impact of 27.44 g CO2 eq/MJ for anhydrous ethanol and 4.68 g CO2 eq/MJ for electricity, representing 94.11% and 5.81% of the total impacts of the analyzed process, respectively. In comparison, the classical energy allocation method calculated an impact of 21.89 g CO2 eq/MJ for both products, representing 75.08% for ethanol and 24.92% for electricity. It was found that the proposed method allowed for separating the impacts associated with each production process, without penalizing one product for the impacts generated by the other product. Furthermore, the method enables the visualization of impact flows through the process, aiding in identifying sustainability bottlenecks and optimizing the process.
Method for allocation of environmental impact metrics in multi-product industrial units
Keywords: Avaliação de ciclo de vida; Alocação; Biorrefinarias; Processos multiproduto; Impactos ambientais; Life cycle assessment; Allocation; Biorefinery; Multiproduct processes; Environmental impact; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA::PROCESSOS BIOQUIMICOS